(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the knowledge and perception of men regarding vasectomy as contraceptive method Study Design: Descriptive study. Setting and Duration: The study was carried out at Family Planning center, Sir Ganga Ram Hospital, Lahore from January 2010 to July 2010. Sample: All the men attending family planning center during the study period were included in the study. Methods: It is important to understand male perceptions in order to address the problems involved in implementation of male contraceptive methods. In this study, to determine the knowledge and perception of the males regarding vasectomy, the participants were divided into two groups. The husbands who came for vasectomy were put in first group while the husbands who accompanied their wives for bilateral tubal ligation were in second group. There were one hundred and forty husbands in first group while seventy in second group. These interviews were conducted at Family Planning center, Sir Ganga Ram Hospital, Lahore from the month of January 2010 to July 2010. Results: This study revealed that there was a good knowledge and perception regarding vasectomy among the men who came for vasectomy. These husbands also have knowledge about the negative information regarding vasectomy. On the other hand the second group of husbands who accompanied their wives for bilateral tubal ligation had a poor knowledge regarding vasectomy, its advantages, complications and negative information. Conclusion: Based on the results of this study, it is important to campaign for the male permanent contraceptive methods (vasectomy) among couples in order to improve the family planning program.